A comemoração dos mortos em tempos medievais - Maria do Rosário Barbosa Morujão (Medievalista)
This article is an exploratory approach to the study of the commemoration of the dead in the Middle Ages, using the Cathedral of Coimbra and its obituaries as an example. Based on this case, an effort is made to identify the kinds of information that can be obtained from such sources and questions are raised regarding their limitations for reconstructing the ceremonies related to liturgical services for the souls of the dead.